Başkurt Destanlarında Kahramanların Olağanüstü Doğumu - Bars, Mehmet Emin (Muş Alparslan Üniversitesi, 2018)
Inancient times when the tribal life was dominant, the child meant to be strongagainst the enemy. In a society where there are constant wars, and a large partof life is in flocks, the child is in a social expectation. In the Turkish epictradition, extraordinary births of heroes are seen as a fixed rule. In ourstudy, the birth of the hero, who gave the title to the narrative in the epicsthat include mythological, social life, khan's time and historical-heroicissues from the Baskurt epics, was examined. Some of the Baskurt epic heroescome to the world in extraordinary ways, such as being born of light, good newsby spirits, born of trees, born of a dead mother. The unusual births of heroesare also indicative of their future success. The heroes were sent to the earthto glorify the Turkish nation by receiving sacrifice from God. The heroic typein Baskurt epics is consistent with the heroic model in Turkish epics from manydirections.

Kabilehayatının egemen olduğu eski dönemlerde çocuk sahibi olmak, düşmana karşı çokve güçlü olmak anlamına gelmekteydi. Sürekli savaşların olduğu, yaşamın büyükbölümünün akınlarda geçtiği toplumlarda, çocuk toplumsal bir beklentihalindedir. Türk destan geleneğinde kahramanların olağanüstü doğumları sabitbir kural olarak görülmektedir. Çalışmamızda Başkurt destanlarından mitolojik, sosyal hayat, han ve beylerin zamanı ile tarihî-kahramanlık konularını içerendestanlarda anlatıya ismini veren kahramanların doğumu incelenmiştir. Başkurtdestan kahramanlarının bir kısmı ışıktan doğma, iyeler tarafından müjdelenme, ağaçtan doğma, ölen anneden doğma gibi olağanüstü biçimde dünyaya gelmektedir.Kahramanların olağan dışı doğumları onların gelecekte göstereceği başarılarında habercisidir. Kahramanlar, Tanrı’dan kut alarak Türk milletini yüceltmekiçin yeryüzüne gönderilmiştir. Başkurt destanlarındaki kahraman tipi birçokyönden Türk destanlarında yer alan kahraman modeli ile uyum göstermektedir.
The Extraordinary Birth of the Heroes in the Baskurt Epics
anemon
Keywords: Baskurt; Epic; Hero; Birth; Başkurt; Destan; Kahraman; Doğum